Transient performance of an impinging receiver: An indoor experimental study. (15th February 2018) - Wang, Wujun; Malmquist, Anders; Aichmayer, Lukas; Laumert, Björn
Highlights: An indoor transient performance test of an impinging receiver has been done. The impinging receiver can offer an air outlet temperature of 810 °C. 'Cold startup' operation is harmful to the receiver and should be avoid. The temperature changing rate is within 3 °C/s (startup) and 4 °C/s (turn off). The receiver efficiency is expected to be 74.1%. Abstract: The impinging receiver is a new member of the cavity solar receiver family. In this paper, the transient performance of a prototype impinging receiver has been studied with the help of a Fresnel lens based solar simulator and an externally fired micro gas turbine. The impinging receiver can offer an air outlet temperature of 810 °C at an absorber temperature of 960 °C. The radiative-to-thermal efficiency is measured to be 74.1%. The absorber temperature uniformity is good but high temperature differences have been detected during the 'cold startup' process. The temperature changing rate of the receiver is within 3 °C/s for the startup process and 4 °C/s for the shut-down process. In order to avoid quenching effects caused by the impinging jets, the micro gas turbine should be turned off to stop the airflow when the radiative power is off.